Réponses

Meilleure réponse !
2013-06-23T18:52:14+02:00

 

1) a² + 2ab + b² = (a+b)²

Exemple :

9x² + 6x + 1 = (3x + 1)²

2) a² -2ab +b² = (a-b)²

Exemple :

25 - 10y +y² = (5-y)²

3) a² - b² = (a+b)(a-b)

Exemple :

36 - 4z² = (6+2z)(6-2z)

 ca peut aussi etre le contraire!

voilà j'espere t'avoir aider!

2013-06-23T20:32:48+02:00

(a + b)² = a² + 2ab + b²

(a - b)² = a² - 2ab + b²

(a - b)(a + b) = a² - b²

 

EXEMPLES :

 

(3x + 2)² = 9x² + 12x + 4

(3x - 2)² = 9x² - 12x + 4

(3x + 2)(3x - 2) = 9x² - 6x + 6x - 2 = 9x² - 2